Estimation of articulated angle in six-wheeled dump trucks using multiple GNSS receivers for autonomous driving. (2nd December 2021) - Suzuki, Taro; Ohno, Kazunori; Kojima, Shotaro; Miyamoto, Naoto; Suzuki, Takahiro; Komatsu, Tomohiro; Shibata, Yukinori; Asano, Kimitaka; Nagatani, Keiji
Abstract : Due to the declining birthrate and aging population, the shortage of labor in the construction industry has become a serious problem, and increasing attention has been paid to automation of construction equipment. We focus on the automatic operation of articulated six-wheel dump trucks at construction sites. For the automatic operation of the dump trucks, it is important to estimate the position and the articulated angle of the dump trucks with high accuracy. In this study, we propose a method for estimating the state of a dump truck by using four global navigation satellite systems (GNSSs) installed on an articulated dump truck and a graph optimization method that utilizes the redundancy of multiple GNSSs. By adding real-time kinematic (RTK)-GNSS constraints and geometric constraints between the four antennas, the proposed method can robustly estimate the position and articulation angle even in environments where GNSS satellites are partially blocked. As a result of evaluating the accuracy of the proposed method through field tests, it was confirmed that the articulated angle could be estimated with an accuracy of 0.1 ∘ in an open-sky environment and 0.7 ∘ in a mountainous area simulating an elevation angle of 45 ∘ where GNSS satellites are blocked. GRAPHICAL ABSTRACT: UF0001